Artificial intelligence and clean production on the way to sustainability: a systematic literature review (LACCEI, 2024)
It is inevitable that new technologies are increasingly incorporated into the activities of institutions and people, this fact represents a challenge for sustainability, since an adequate use of advances will allow a more respectful development with the environment. Considering the above, the aim of this work is to investigate the research trends corresponding to artificial intelligence, clean production, and sustainable performance. For this, a bibliometric analysis of 110 papers was carried out in the scientific databases Scopus and Web of science. To carry out the process of unification, cleaning, and graphic visualization, the technological tools Vantage Point, Biblioshiny in R, and VoSviewer were used. The results present the topic addressed as a current trend in the scientific field in recent years. The analysis by countries exposes the Asian continent as a world leader. On the other hand, the study of keywords highlights the importance of the three fundamental pillars of the research with a possible non-empirical relationship. The results show the proximity between artificial intelligence, clean production, and sustainability.